The pregorexia - anorexia during the pregnancy - Mandera, Amanda; Pawlikowska, Anna; Szuster, Ewa Magdalena; Całkosiński, Aleksander; Kostrzewska, Paulina; Majewski, Maciej (Journal of Education, Health and Sport, 2019)
Introduction and purpose: Eating disorders are a serious problem in the developing world. The media are flooding the public images of thinness promoting it as a healthy, fashionable and perfect. This contributes to the increasing prevalence of eating disorders like anorexia, bulimia, anorexia nervosa or atypical bulimia nervosa. The frequency of appearance of these diseases is unknown. It is suspected that it occurs in the range of a few percent. Description of the state of knowledge: Pregorexia has a very similar symptoms to other eating disorders. The patients are trying to alleviate the impact of pregnancy on the body. Women try to control their weight by reducing calories intake, exercising, taking laxatives or diuretics. Low mother’s body weight could cause hypotrophy malformations due to micronutrient deficiency - eg. neural tube defects, cognitive disorders, premature birth or even miscarriage. The placenta develops slowly, there is a risk of placenta abruption. Pregorexia can cause maternal anemia, impaired bone mineralization or postnatal depression. Women which are suffering from pregorexia often give birth girls, which can be associated to the lower resistance of boys maternal malnutrition and loss of the pregnancy. Conclusions: Pregorexia is not a phenomenon that is occurring very often, but it is a big risk to the fetus. Increasingly, young mothers have a problem with acceptance of changes in their bodies during pregnancy. The role of a doctor in an interview with a pregnant woman is to ask about nutrition and weight gain as factors directly affecting the child. Pregnant women with eating disorders should be under a special psychological care, during pregnancy and after birth.